Modeling and experiment of piezoelectric actuators in active repair of isotropic and composite structures - Ahmed, Abuzaid Ahmed (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Traditionally, a cracked structure is repaired using metal bolts and rivets as fastening reinforcement. This process involves drilling fastener holes that cause a change in the stress distribution and simultaneously worsening the stress concentration in the neighbourhood of the repaired area. A composite patch, bonded externally over the crack area, is considered more effective in cracked structure repairs. However, it also alters the load path since the load is transferred to the composite reinforcement patch; which is not flexible and cannot be adjusted to the change in the external loads. Therefore, active repair using piezoelectric actuators can play a significant role as an alternative method in reducing the crack damage propagation in engineering structures. In this study, the active repair and control of a Mode-I opening displacement for centre/edge cracked and delaminated structures is conducted. The repair and control technique is performed utilizing the piezoelectric electromechanical behaviour. The study is divided into three major parts. In the first and second parts, accurate mathematical models are proposed. The models relate the Mode-I stress intensity factor and piezoelectric actuator parameters for centre and edge cracked isotropic plates respectively. The electromechanical models are based on Linear Elastic Fracture Mechanics (LEFM), the virtual crack closure method, the singular stress at the crack tip, and the coupling effects of the piezoelectric actuator. In addition, the superposition method is applied for the stress intensity factor produced by the piezoelectric actuator as the only external load on the cracked plate and the stress intensity factor due to the far field tension load. The proposed analytical models are then verified by finite element analysis (FEA). The results demonstrate a good agreement between the analytical and finite element models. The work then proceeds by conducting experimental investigations in order to validate the proposed analytical model and the finite element analysis. The experimental results show that the proposed analytical solution is applicable with reasonable accuracy. Moreover, a parametric study is conducted to understand the influence and study the efficiency of the piezoelectric actuator on mitigation of the Mode-I SIF. The parametric results indicate that the applied voltage, actuator shape, and thickness have significant influence on the active repair performance. The third part of this work focuses on the study of the active control of opening the Mode-I of delaminated composite structures using finite element analysis. The electromechanical properties of the piezoelectric actuator are employed to produce a bending moment through the external voltage to counteract the delamination's propagation. Furthermore, experimental investigations are performed in order to validate and verify the proposed methodology. The results show that the active delamination control is dependent on the actuator characteristic. In summary, this thesis has demonstrated the feasibility and practicality of the active repair of the edge/centre cracked isotropic plate under Mode-I loading using analytical, numerical simulations, and experimental studies. Moreover, the active control of the Mode-I opening of the delaminated composite structure was also proof that the method is realistic using FEA and experimental work.